Impact of Childhood Sexual Assault on Sexual Function in the Czech Male Population - Watcharaphol Alexandre Kamnerdsiri, MD, MSc, IFAPA; Christopher Fox, PhD, FRSPH; Petr Weiss, PhD, DSc (Sexual Medicine, 2020)
Introduction: This study explores the impact of childhood sexual assault (CSA) on men's sexual function. There is limited understanding on the impact of CSA perpetrated against boys on later adult male sexual function, as there is a dearth of research on this topic. It was hypothesized that men reporting a history of CSA were more likely to report sexual function issues than men with no history of CSA. Material and methods: A cross-sectional survey study of 1,004 Czech men aged between 15 and 85 years (M = 42.8 years; Standard deviation = 17.6 years) have been conducted. The participants anonymously answered a questionnaire on multiple aspects of their life and sexuality. This questionnaire included sought data on history of CSA and self-reported intravaginal ejaculation latency time and the 5-item International Index of Erectile Function. Results: 25 men (2.5%) indicated a history of CSA. 71% of the perpetrators where known by the victims, with a minority declaring the crime to authorities (37.5%). Half of those reporting assault also reported sexual function issues in the present or at some time in their life. Significant correlations were recorded between a history of CSA and erectile dysfunction but not significantly with premature ejaculation. Conclusions: Men who reported a history of CSA are more likely to report sexual function issues than those who do not. The identified association between CSA and sexual function issues in adult life contributes to the small body of literature on the topic. When taking a sexual history, it is recommended to practitioner to include questions about CSA, considering its correlation with erectile dysfunction. An understanding of the relationship between CSA and adult sexual function helps practitioner to improve his patient's well--being and life satisfaction.Kamnerdsiri WA, Fox C, Weiss P, et al. Impact of Childhood Sexual Assault on Sexual Function in the Czech Male Population. J Sex Med 2020;8:446–453.